Finding the Culprit: Cushing Syndrome Secondary to Lung Carcinoid Tumor - Richard Vaca, MD; Nirali A. Shah, MD (AACE Clinical Case Reports)
Background/Objective: Cushing syndrome resulting from ectopic adrenocorticotropic hormone (ACTH) secretion (EAS) is a rare condition, and its occurrence in adolescents is even more uncommon, representing <1% of cases. We describe a case of EAS from a lung carcinoid tumor leading to Cushing syndrome in a young woman, which was successfully treated with excision of the tumor. Case Report: An 18-year-old woman presented with mood disturbances, weight gain, and fatigue for 6 months. Workup revealed high levels of urinary free cortisol (>900 μg/dL; normal range, <45 μg/dL) and midnight salivary cortisol (0.755 μg/dL; normal range, <0.09 μg/dL). The ACTH and cortisol levels remained elevated after a low-dose dexamethasone suppression test. Magnetic resonance imaging of the pituitary gland did not reveal any adenoma and inferior petrosal sinus sampling showed no central-to-peripheral gradient. A diagnosis of EAS was made. Subsequent body imaging noted a 1-cm lung nodule. Due to symptoms of severe hypercortisolism including hypokalemia and worsening mood changes, the patient was started on metyrapone as a bridge to surgery. A few weeks later, the patient underwent successful surgical resection, after which symptoms promptly resolved. Pathology report later confirmed an atypical lung carcinoid tumor. The patient remained in remission at 1-year follow-up. Discussion: Medical therapy aids in managing severe hypercortisolism in ACTH-secreting tumors until definitive surgical treatment can be undertaken. Conclusion: This case underscores the critical importance of promptly recognizing EAS and the resulting severe hypercortisolism symptoms because early surgical intervention can lead to a cure.